Gender gaps in English as a second foreign language attainment: some Oujda High Schools case study - Hicham Dahmani; Youssef Ben Chbir; Aziz Bayour (Journal of Science and Education (JSE), 2022)
Several studies and research have been conducted on the issue of gender gap attainment, most of which have concluded that female students are relatively higher achievers compared to males. This gap is attributed to different explanations depending on the angles from which it is viewed, amongst which is the average use of language learning strategies (LLS). Therefore, the current study attempts to find out and analyze the reasons why female and male students perform differently in the English classes in Oujda high schools. It also aims to discover who exploits LLS more in learning English as a foreign language. To effectively reach this goal, the researchers use a self-developed observation checklist to identify who outperforms the other and a structured interview to discern who uses LLS more effectively. As a result, two points emerged in this research paper. The current study attempts to find out about female-male differences in English attainment. Besides, it seeks explanations for male and female performance in the English classes in Oujda high schools. It also aims to discover who exploits LLS more in learning English as a foreign language. To fill this gap, a number of 960 students were observed, and 32 students were interviewed. The study is approached using the mixed-method of quantitative and qualitative design, where a descriptive approach is used. Data is gathered through both instruments observation and interviews in five high schools. To effectively reach this goal, the researchers use a self-developed observation checklist to identify who outperforms the other and a structured interview to discern who uses LLS more effectively. As a result, two points emerged in this research paper. First, this research paper proves that females outperform males in English classes. Second, females use more learning strategies than males. The researchers infer from the results that there is an attainment gap, namely, male students underachieve females.